SECONDARY LEDEBURITE FORMATION DURING VARIOUS WELDING TECHNIQUES - Karpe, Blaž (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The occurrence and formation sequence of secondary ledeburite in the heat affected zone of chromium ledeburitic tool steel W.Nr. 1.2379 (OCR12 VM) after welding with SAW, TIG, microplasma and laser welding techniques is presented in this paper. Special attention was paid on the behaviour of carbides. The occurrence of secondary ledeburite is a result of local enrichment of the austenite matrix with alloying elements, due to partial or complete dissolution of primary/eutectic carbides. The results show that the largest amount of secondary ledeburite is formed during submerged arc welding, followed by TIG and microplasma welding technique. Welding by laser technique, with appropriate technological parameters, could prevent secondary ledeburite formation.